Pattern and prevalence of tobacco use and associated oral mucosal lesions: a hospital based cross sectional study at a tertiary care hospital in central India - Mishra, Ambrish; Sharma, Divashree; Tripathi, Geeta Mishra; Adhikari, Paharam; Kabirpanthi, Vikrant; Kumar, Manish (International Journal of Research in Medical Sciences, 2017)
Background: Tobacco is known to mankind since ages. Despite the widespread awareness about tobacco related health hazard and vigorous efforts to regulate its use in various form of strict tobacco control legislation; its use is increasing at an alarming rate. Tobacco use carries a high risk of major health-related illness and several forms of cancers. The epidemic of tobacco use in India is inflicting a huge damage on the human health and the associated health care costs are creating a huge financial burden on the government. The objective of the study was to assess the prevalence of tobacco consumption and related oral mucosal lesions among patients reporting to dental outpatient department of a tertiary care centre in Rewa (M.P.). Methods: Out of the total patients reporting to the outpatient department of dentistry during the study period, 5185 patients were considered for this study, 1285 were found consuming tobacco in one or other form. The consent for participation in the study was given by 1178 tobacco users. They were interviewed through prepared questionnaires and clinically examined for tobacco associated oral lesions. The data were collected, cleaned and compiled. Results: The overall prevalence of tobacco use was 24.78%. Out of the 1178 tobacco users studied, 893 (75.80%) were males and 285 (24.19%) females. Smoked form was the most commonly used tobacco for males (44.56%) while smokeless tobacco was preferred by majority of females (69.12%). 23.94% of the tobacco users were in the age group of 21-30 years. Oral mucosal lesions were seen in 32.51% subjects. Conclusions: The number of tobacco users visiting the dental hospital is reasonably high; Tobacco consumption is a common cause of addiction, preventable illness, disability and death. The public health system should be strengthened for effectively designing, implementing and evaluating tobacco control and prevention programs. All health care professionals should be sensitized and educated for implementing measures for tobacco control and cessation.